FUNCTIONALLY COMPLETE REVASCULARIZATION IN PATIENTS PRESENT WITH ST-ELEVATION MYOCARDIAL INFARCTION (MI) AND MULTIVESSEL CORONARY ARTERY DISEASE (The Research of Medical Science Review, 2024)
Introduction: ST-elevation myocardial infarction (STEMI) is a medical emergency characterized by the abrupt occlusion of a coronary artery, resulting in significant myocardial ischemia and necrosis. Objective: The main objective of the study is to find the functionally complete revascularization in patients present with ST-elevation myocardial infarction (MI) and Multivessel coronary artery disease. Methodology: This prospective observational study was conducted at the Sindh Institute of Cardiovascular, Larkana from February 2024 to 30 November 2024. Data were collected from 80 patients. Data were collected prospectively using standardized case report forms. Clinical, angiographic, and procedural data were recorded, including patient demographics, baseline clinical characteristics, lesion-specific details, and procedural outcomes. Results: Mean age of patients was 59.08 ± 9.23 years, distributed across immediate (n=45) and staged (n=35) revascularization groups. Males comprised 75% of the total, with a slightly higher proportion in the staged group (77%). Diabetes Mellitus was present in 40% of participants, with comparable rates between the groups. Hypertension affected 55% of the participants, while 50% had a history of smoking, showing minimal variation across groups. The outcomes showed high procedural success rates in both groups (98% for immediate and 97% for staged revascularization, p=0.78). Conclusion: It is concluded that functionally complete revascularization significantly improves outcomes in STEMI patients with MVCAD by addressing physiologically significant lesions, reducing ischemic events, and optimizing care.